Direct electrochemical measurement of metanephrines in spot urine samples for the diagnosis of phaeochromocytomas - Zheng-Hu Shi (Nature Portfolio, 2017)
Abstract Metanephrines (MNs) were suggested as a potential first-line biochemical index for the diagnosis of phaeochromocytomas (PHEO). In this study, we developed a simple electrochemical method for the quantitative measurement of MNs in spot urine samples. As MNs contain a hydroxyphenyl group, they could be oxidized at a certain potential to quinines, which could be further detected by the differential pulse voltammetry (DPV) method using unmodified screen-printed carbon electrode (SPCE). Meanwhile, the solid phase extraction (SPE) technique was used to eliminate the matrix effect in the samples. Consequently, free MNs from the extracted urine sample were screened in a linear range from 0.25 mg/L to 12.5 mg/L. The lowest limit of quantification (LLOQ) for MNs was 0.25 mg/L and the limit of detection (LOD) was 0.05 mg/L. Both the precisions and recoveries were sufficient for clinical applications. The urine samples from 22 patients with PHEO and 63 controls were analyzed by the proposed method. The area under the ROC curve was 0.981 (95% CI, 0.958–1.000) with the sensitivity of 95.5% and the specificity of 92.4% at the cut-off value of 0.404 mg/L in these urine samples. Overall, the proposed method provides a cost-effective, rapid and simple tool for clinical diagnosis of PHEO.